2017
DOI: 10.22436/jnsa.010.05.42
|View full text |Cite
|
Sign up to set email alerts
|

Boundedness of higher order Riesz transforms associated with Schrodinger type operator on generalized Morrey spaces

Abstract: Let L 2 = (−∆) 2 + V 2 be a Schrödinger type operator, where V = 0 is a non-negative potential and belongs to the reverse Hölder class RH q for q n/2, n 5. The higher Riesz transform associated with L 2 is denoted by R = ∇ 2 L 2 ∇ 2 . In this paper, we investigate the boundedness of higher Riesz transforms and their commutators on the generalized Morrey spaces related to some non-negative potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In [2], Chen and Jin showed the boundedness of µ L j and [b, µ L j ] on the Morrey spaces related to certain nonnegative potentials. In [9], we introduced the generalized Morrey space related to nonnegative potential V, which covers the general Morrey space; see [2,7,8,11].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…In [2], Chen and Jin showed the boundedness of µ L j and [b, µ L j ] on the Morrey spaces related to certain nonnegative potentials. In [9], we introduced the generalized Morrey space related to nonnegative potential V, which covers the general Morrey space; see [2,7,8,11].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…They have showed that the singular integral operators are not only bounded in weighted Lebesgue spaces but also in weighted Morrey spaces. In addition, lots of Morrey type spaces associated to a Schrödinger operator have been also studied (see [2,19,21,27,33]) to extend the wellknown Morrey spaces. In recent years the problem related to Schrödinger operator has attracted a great deal of attention of many mathematicians; see [3,4,5,6,7,9,10,22,29,35] and references therein.…”
Section: Introductionmentioning
confidence: 99%